Survival in Patients With Suspected Myocardial Infarction With Nonobstructive Coronary Arteries: A Comprehensive Systematic Review and Meta-Analysis From the MINOCA Global Collaboration. Issue 11 (November 2021) - Pasupathy, Sivabaskari; Lindahl, Bertil; Litwin, Peter; Tavella, Rosanna; Williams, Michael J.A.; Air, Tracy; Zeitz, Christopher; Smilowitz, Nathaniel R.; Reynolds, Harmony R.; Eggers, Kai M.; Nordenskjöld, Anna M.; Barr, Peter; et al.
Abstract : Background: Suspected myocardial infarction (MI) with nonobstructive coronary arteries (MINOCA) occurs in ≈5% to 10% of patients with MI referred for coronary angiography. The prognosis of these patients may differ to those with MI and obstructive coronary artery disease (MI-CAD) and those without a MI (patients without known history of MI [No-MI]). The primary objective of this study is to evaluate the 12-month all-cause mortality of patients with MINOCA. Methods: Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, the terms "MI, " "nonobstructive, " "angiography, " and "prognosis" were searched in PubMed and Embase databases from inception to December 2018, including original, English language MINOCA studies with >100 consecutive patients. Publications with a heterogeneous cohort, unreported coronary stenosis, or exclusively focusing on MINOCA-mimicking conditions, were excluded. Unpublished data were obtained from the MINOCA Global Collaboration. Data were pooled and analyzed using Paule-Mandel, Hartung, Knapp, Sidik & Jonkman, or restricted maximum-likelihood random-effects meta-analysis methodology. Heterogeneity was assessed using Cochran's Q and I 2 statistics. The primary outcome was 12-month all-cause mortality in patients with MINOCA, with secondary comparisons to MI-CAD and No-MI. Results: The 23 eligible studies yielded 55 369 suspected MINOCA, 485 382 MI-CAD, and 33 074 No-MI. Pooled meta-analysis of 14 MINOCA studies accounting for 30 733 patients revealed an unadjusted 12-month all-cause mortality rate of 3.4% (95% CI, 2.6%–4.2%) and reinfarction (n=27 605; 10 studies) in 2.6% (95% CI, 1.7%–3.5%). MINOCA had a lower 12-month all-cause mortality than those with MI-CAD (3.3% [95% CI, 2.5%–4.1%] versus 5.6% [95% CI, 4.1%–7.0%]; odds ratio, 0.60 [95% CI, 0.52–0.70], P <0.001). In contrast, there was a statistically nonsignificant trend towards increased 12-month all-cause mortality in patients with MINOCA (2.6% [95% CI, 0%–5.9%]) compared with No-MI (0.7% [95% CI, 0.1%–1.3%]; odds ratio, 3.71 [95% CI, 0.58–23.61], P =0.09). Conclusions: In the largest contemporary MINOCA meta-analysis to date, patients with suspected MINOCA had a favorable prognosis compared with MI-CAD, but statistically nonsignificant trend toward worse outcomes compared to those with No-MI. Registration: URL: https://www.crd.york.ac.uk/PROSPERO/ ; Unique identifier: CRD42020145356. Abstract : Supplemental Digital Content is available in the text.